The effect of shape, length and diameter of implants on primary stability based on resonance frequency analysis - Barikani, Hamidreza (Medknow Publications & Media Pvt Ltd, 2014)
BACKGROUND: The aim of this in vitro study was to evaluate the effect of shape, diameter and length of implants on their primary stability based on resonance frequency analysis. MATERIALS AND METHODS: Replace select tapered and Branemark MK III implants were selected. Each of these two selected groups was divided into nine subgroups based on the implant length (IL) (short, medium and long) and the implant diameter (ID) (narrow platform [NP], regular platform [RP] and wide platform [WP]). Five implants were assigned to each of the nine subgroups. Implants were placed in artificial bone blocks with bone quality similar to D3 bone. Immediately after the implant placement, its primary stability was measured using Osstell Mentor equipment. T-test and Tukey's honest significant difference Post hoc were performed for data analysis. Statistical significance was defined at P < 0.05. RESULTS: Replace select system showed significantly higher primary stability compared to the Branemark system, when using the short implants for all three diameters (P ≤ 0.004). However, in medium length implants there were no significant differences between the two implant systems (P ≥ 0.31). In long implants, only when the NP and RP implants were used, the Replace Select system showed significantly higher primary stability compared to the Branemark system (P = 0.000). In the replace select system, long implants had a significantly higher primary stability compared to medium and short length implants (P ≤ 0.003). In the NP and RP Branemark implants, short implants showed significantly lower primary stability compared to medium and long implants (P ≤ 0.002). However, in WP Branemark implants, primary stability increased significantly with increasing the IL from short to medium and from medium to long (P = 0.000). There were also significant differences between NP and the two other wider implants in both systems (P = 0.000). CONCLUSION: The use of tapered implants is recommended, especially, when the use of short implants is necessary. The use of RP implants is also preferred to WP implants, because thicker bone wall will remain in place when applying RP implants. Furthermore, no significant difference was observed between RP and WP implants.